Detection of long storage and sunflower adulteration of olive oils using ultra-violet (UV) spectroscopy method - M. Al-Bachir; Y. Othman (International Journal of Food Studies)
The purpose of the study was to evaluate the effects of Syrian Kaissy olive oil (SKOO) adulteration and long storage periods on the basic quality indices namely, peroxide value (PV), acid value (AV), and absorbance of UV (K232, K270, ∆K and R (K232/K270) values). This study revealed that the quality indexes, including AV, PV, K232, K270 and ∆K values, of all SKOO specimens increased with increasing storage time. It was revealed that the K232, K270 and ∆K values of SKOO specimens stored for 1 and 2 years remained under the limits, established by International Olive Council (IOC), of 2.5, 0.22 and 0.01 units, respectively. While in some cases, the K232, K270 and ∆K values exceeded their respective limits after 8, 9 and 10 years of storage. The index of R (K232/K270) decreased with time of storage.